PELATIHAN PENYUSUNAN PROSEDUR OPERASIONAL STANDAR BERBANTUAN APLIKASI BIZAGI MODELER DI SEKOLAH INDONESIA MAKKAH, ARAB SAUDI - Setiawan, Aditya Chandra; Hariyati, Nunuk; Wulandari, Ayu (Universitas Negeri Surabaya, 2025)
The partner for community service in 2025 is SILN Makkah, Saudi Arabia. The issue faced by the partner is the suboptimal utilization of technology and digitalization in managing the institution. This condition serves as the basis for the implementation of community service, wherein the research team has specific expertise in the management of educational institutions, particularly the challenges faced by educational institutions at SILN Makkah, Saudi Arabia. Based on the priority issues faced by the partner, the method agreed upon by the PKM team and the partner is Training and mentorship. In addition to direct training, the method used is online mentoring until the partner can prepare the standard operating procedures with the help of the Bizagi Modeler application. The mandatory outputs include Articles in the Journal of Community Service: Transformation and Innovation, Media News, and Activity Videos. The results obtained indicate that the SIM Makkah partners have achieved an enhanced understanding and skills regarding the quality of academic service procedures (SOP) through training and mentoring over 32 hours, both online and offline. Consequently, a level of satisfaction regarding the implementation of the training and mentoring has been achieved in the 'satisfactory' category. Keywords: Training, Operational Procedures, Bizagi Modeler